The influence of cultural values on Enterprise System adoption, towards a culture – Enterprise System alignment theory. (April 2022) - Vos, Janita F.J.; Boonstra, Albert
Abstract: During the last decades, organizations worldwide have replaced their fragmented and home-grown information systems with standardized Enterprise Systems that span the entire organization. The logics embedded in Enterprise Systems, such as a centralized and integrated view on the firm, standardized organization-wide working processes, and data sharing, may or may not be congruent with the cultural context of the user organization. Especially in case of a limited alignment, the adoption and full use of the Enterprise System will require specific attention from implementers. By developing a theoretical explanation of how responses to Enterprise Systems are influenced by cultural values, we contribute to the development of a cultural alignment theory of Enterprise Systems. Drawing on Hofstede's cultural values framework, we analysed 85 published cases from firms operating in different cultural contexts, which resulted in the modelling of two contrasting archetypical cultural profiles: one that is more, and one that is less, receptive to the logics embedded in Enterprise Systems. Our model provides implementers with the necessary insights to develop implementation strategies that take the cultural context into account. Highlights: We examine how cultural values influence Enterprise System (ES) adoption. Enterprise Systems are designed according to specific logics. ES logics may align or conflict with the cultural values of adopting firms. Accepting and resisting archetypical cultural profiles are identified. The model gives implementers insights into culture-aware implementation strategies.